Experimental Infection of California Ripe Olive Cultivars with Xylella fastidiosa Subspecies pauca De Donno and Acquisition by Glassy-Winged Sharpshooter - Lindsey Burbank; Elizabeth E. Rogers; Aaron J. Sechler; Mayra Magdeleno; Rodrigo Krugner (PhytoFrontiers)
Strains of Xylella fastidiosa subspecies pauca can infect olive trees, and an introduction of this pathogen has caused significant damage to the olive industry in Europe. Although this subspecies is not known to be present in North America, the environment, plant hosts, and insect vectors in the United States olive-growing regions (mainly California) are conducive to X. fastidiosa spread and disease damage. This study evaluated several risk factors for X. fastidiosa disease in the California olive industry, including infection of the common cultivars and acquisition by insect vectors. Olive cultivars Manzanillo, Sevillano, and Mission all exhibited disease symptoms after inoculation with X. fastidiosa strain De Donno obtained from the olive disease outbreak in southern Italy. Glassy-winged sharpshooters were able to acquire X. fastidiosa De Donno from infected olive plants as soon as 30 days after plant inoculation. This information is valuable for risk assessment and disease management planning in the event of a future introduction of olive-pathogenic strains of X. fastidiosa to the United States. [Figure: see text] The author(s) have dedicated the work to the public domain under the Creative Commons CC0 “No Rights Reserved” license by waiving all of his or her rights to the work worldwide under copyright law, including all related and neighboring rights, to the extent allowed by law, 2024.